Circling the bases : essays on the challenges and prospects of the sports industry - Zimbalist, Andrew S. (Temple University Press, 2011)
In Circling the Bases, leading sports economist Andrew Zimbalist continues his discussion and analysis of the major issues and challenges confronting the sports industry in the second decade of the 21st century. Presenting a general overview of the sports business at both the college and professional levels, this volume places concerns such as the antitrust status of sports leagues, the stalled progress of gender equity in college sports, and the control of Performance Enhancing Drugs in historical context.